Book Review: Social Learning Towards a Sustainable World: Principles, Perspectives and Praxis by Arjen E.J. Wals. (25th April 2008) - Dillon, Justin
Social Learning Towards a Sustainable World: Principles, Perspectives and Praxis, by Arjen E.J. Wals. The Netherlands, Wageningen Academic Publishers, 2007. ISBN 978-90-8686-031-9